2020
DOI: 10.3350/cmh.2019.0023
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic strategies and outcomes in ABO-incompatible living donor liver transplantation

Abstract: In the past, adult ABO incompatible living donor liver transplantation (ABO-I LDLT) had poor graft survival and low patient survival due to hyperacute rejection and a high risk of vascular biliary complication, and it was considered a contraindication. 1-4 Susceptibility to rejection, including severe hepatic necrosis and diffuse intravascular coagulation disorder within the graft, appears to be due to the blood group antigen expressed in the vascular endothelium and bile ducts after transplantation. 5,6 Vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
(61 reference statements)
0
34
0
Order By: Relevance
“…Methylprednisolone therapy was initiated on the operation day at a dose of 500 mg/day and then tapered to 4–8 mg/day within 1–2 months postoperatively. In case of ABO-incompatible LDLT, rituximab prophylaxis and frequent total plasma exchange were conducted for desensitization ( 6 ). When HCC recurs, tacrolimus trough level was lowered compared to patients without HCC recurrence and everolimus was added.…”
Section: Methodsmentioning
confidence: 99%
“…Methylprednisolone therapy was initiated on the operation day at a dose of 500 mg/day and then tapered to 4–8 mg/day within 1–2 months postoperatively. In case of ABO-incompatible LDLT, rituximab prophylaxis and frequent total plasma exchange were conducted for desensitization ( 6 ). When HCC recurs, tacrolimus trough level was lowered compared to patients without HCC recurrence and everolimus was added.…”
Section: Methodsmentioning
confidence: 99%
“…Contrarily, other reports indicated that ABO-incompatible transplants do not require specialized immunosuppressive therapy. In one study, the survival rates of the transplanted graft and the recipient were comparable with either those in ABO-compatible-matched controls or patients with low baseline antiblood group antibody titers [ 14 ], whereas a second study recorded a graft survival rate of 100% at 36 months after transplantation [ 15 ].…”
Section: Abo Blood Group-incompatible Antibodies In the Field Of Tmentioning
confidence: 99%
“…Additionally, antibodies against ABO blood group antigens, which are representative of IgM and IgG antibodies, induce the development of AMR, causing transplanted graft failure in ABO-incompatible liver transplant recipients [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 ] With improvements in desensitization management, including plasmapheresis and immunosuppression regimens, the graft survival rate in ABOi LDLT has improved greatly. [ 5 ] Desensitization measures include splenectomy, given the spleens function in the production and storage of antibodies, B cells and plasma cells as well as in blood filtration, phagocytosis, red blood cell destruction, antigen uptake and hemopoiesis. However, splenectomy increases the risk of complications, including infection, portal vein thrombosis and bleeding.…”
Section: Introductionmentioning
confidence: 99%